The financial economics of sovereign asset value: functional perspectives and market outcomes - Peter N Posch; Roger J Bowden; Eva-Maria Kalteier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The asset value of government has traditionally been seen as the accounting value of public assets. We develop a detailed financial economics view on sovereign asset values using market measures to arrive at implied sovereign asset values. We establish definition and dependencies within the resulting framework. Unlike the private sector, it is not a necessary public sector objective to maximise functional asset value as such; indeed some wealthier countries can run a habitually lower asset cover. Governments exposed more to economic shocks need to make more provision for buffering implied equity exposure. The ability to do so endows a real option value to budget flexibility. We identify the economic drivers of the implied asset values and the real option value in a broad sample of industrialized countries. Our theoretical framework and empirical results are instructive for market participants as well as for governments.
Keywords: H63; G01; E62; 330